The Capacity of Periodontal Gel to Occupy the Spaces Inside the Periodontal Pockets Using Computational Fluid Dynamic - Luca Levrini; Luigi Paracchini; Maria Giulia Nosotti (MDPI AG, 2019)
The aim of the current work is to demonstrate the capacity of a new periodontal gel to occupy the spaces inside the periodontal pockets through Computational Fluid Dynamic (CFD). The test gel consists of two resorbable medical grade polymers (PEO, Poly Ethylen Oxide and HPMC, Hydroxy Propyl Metyl Cellulose), Type I Collagen, SAP (Vitamin C), and PBS (Saline Solution), while the control gel is 14% doxyclin controlled release gel, which is used for treating periodontal pockets with probing ≥5 mm after scaling and root plaining. The study examined the fluid dynamic analysis (Computational Fluid Dynamic—CFD) of two different gels, used in dentistry to treat periodontitis, in relation to both the geometry of the periodontal pocket and the function of two different types of needles that are used to distribute the preparation. The periodontal pocket was determined by reading DICOM images taken from the patient’s CAT scan. The results show that the H42® gel comes out uniformly compared to the other gel. Moreover, it is possible to observe how the rheological properties of the gel allow the fluid to spread evenly within the periodontal pocket in relation to the geometry of the needle. In particular, H42® gel exits in a constant way both from the first and the second exit. In fact, it was observed that by changing the geometry of the needle or the type of periodontal gel, the distribution of the gel inside the pocket was no longer homogeneous. Thus, having the correct rheological properties and correct needle geometries both speeds up the gel and optimizes the pressure distribution. Currently, the literature is still lacking, therefore further studies will be needed to confirm these results.